Challenges of logistic processing of the transport package selected by suppliers for international carriage of construction goods by road - Ekaterina Tettsoeva (Управление)
The purpose of the article is to identify the general situations emerging in the practice of road carriers and importing companies that relate to increased risk of damage and destruction of the goods and also to delivery delays because of the mismatch between the transport packaging which is provided by foreign suppliers of construction materials and the goods itself. The article gives pride of place to the recommendations on minimizing of the risks that are connected with transport and consumer packaging of construction materials delivered in Russia from abroad by truck. It has been noted noted that in the face of declining of effective demand for commercial and residential real estate one of the most widespread ways to reduce the costs of construction and, as a result, real estate value is cutting procurement expenditures. The author draws attention to the fact that one of the reasons for occurrence of additional expenses at the stage of procurement of the goods for construction needs could be total or partial incompatibility between, on the one hand, packing and wrapping materials and, on the other hand, both the materials carried and vehicles that are planned to transport the cargo. The article considers the features of general nomenclature groups of imported from Europe construction materials, gives the detailed analysis of the characteristics of the transport and consumer packaging and also the wrapping used in the process of its transportation. The author suggests the algorithm of coordinated actions of suppliers, buyers, local carriers from countries of consignment and logistics operators, which could be applied for reducing of the quantity of the incidents during the logistics handling connected with packing.